2018
DOI: 10.7150/ijbs.22220
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and genetic inhibition of STAT3 sensitizes hepatocellular carcinoma cells to sorafenib induced cell death

Abstract: Hepatocellular carcinoma (HCC) has become the second leading cause of cancer related death, with an increasing death rate in recent years. For advanced HCC, sorafenib is the first-line FDA approved drug, with no more than 3 months' overall survival advantage. Recently, a novel strategy has been proposed to improve sorafenib efficacy through enhancing the ability of sorafenib to induce cell death. STAT3 plays a key role in cancer development and recurrence by promoting cell proliferation, survival and immune ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Inhibition of STAT3 by JAK2 inhibitor, AG490, further induced apoptosis in HCC cell line, Hep3B, by downregulating the expression of anti-apoptotic proteins Bcl-xL and survivin [34]. Additionally, STAT3 has also been implicated in the development of sorafenib resistance in HCC cell line Huh7 by the regulation of anti-apoptotic protein, Mcl-1 [43]. The overexpression of JAK1/2 and constitutive phosphorylation of STAT3 (Tyr705) results in the nuclear localization of STAT3 and expression of Mcl-1 [43].…”
Section: Stat3 In Survival and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of STAT3 by JAK2 inhibitor, AG490, further induced apoptosis in HCC cell line, Hep3B, by downregulating the expression of anti-apoptotic proteins Bcl-xL and survivin [34]. Additionally, STAT3 has also been implicated in the development of sorafenib resistance in HCC cell line Huh7 by the regulation of anti-apoptotic protein, Mcl-1 [43]. The overexpression of JAK1/2 and constitutive phosphorylation of STAT3 (Tyr705) results in the nuclear localization of STAT3 and expression of Mcl-1 [43].…”
Section: Stat3 In Survival and Proliferationmentioning
confidence: 99%
“…Additionally, STAT3 has also been implicated in the development of sorafenib resistance in HCC cell line Huh7 by the regulation of anti-apoptotic protein, Mcl-1 [43]. The overexpression of JAK1/2 and constitutive phosphorylation of STAT3 (Tyr705) results in the nuclear localization of STAT3 and expression of Mcl-1 [43]. Knockdown of STAT3 led to a downregulation of Mcl-1 expression in vitro, rendering the cells sensitive to sorafenib-induced cell death.…”
Section: Stat3 In Survival and Proliferationmentioning
confidence: 99%
“…Sustaining activation of IL-6/STAT3 signaling is crucial for sorafenib resistance. [29][30][31] Recent studies reported that PSMD10 could active IL-6/STAT3 signaling by facilitating the phosphorylation of Rb and IL-6 transcription, thereby promoting sorafenib resistance. 10,32 Based on these studies, we speculated that DANCR may have an effect on IL-6/STAT3 signaling via PSMD10.…”
Section: Dancr Activates Il-6/stat3 Signalingmentioning
confidence: 99%
“…It has been reported that inhibition of STAT3 sensitizes HCC cells to sorafenib induced tumor cell death [ 37 ]. Similarly, STAT3 activation contributed to regorafenib resistance of HCC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%